Is Collaborative Care the Future of Medicine? Lessons Learned from the Care of Children with Colorectal Conditions - Julie M. Choueiki; Stephen Sales; Susan Callicott; David Ashman; Katherine Worst; Andrea Badillo; Briony K. Varda; Allison Mayhew; Thomas O. Xu; Marc A. Levitt (MDPI AG, 2024)
The treatment of patients with colorectal disorders requires care from a wide variety of medical and surgical specialties over the course of their lifetime. This is ideally handled by a collaborative center which facilitates the assessment and development of patient care among multiple specialties which can enhance the quality and implementation of treatment plans, improve communication among different specialties, decrease morbidity, and improve patient satisfaction and outcomes. This collaborative approach can serve as a model for other parts of medicine requiring a similar multi-disciplinary and integrated method of care delivery. We describe the process, as well as the lessons learned in developing such a program.